Prioritizing Diversity in Otolaryngology–Head and Neck Surgery: Starting a Conversation. (13th October 2020) - Truesdale, Carl M.; Baugh, Reginald F.; Brenner, Michael J.; Loyo, Myriam; Megwalu, Uchechukwu C.; Moore, Charles E.; Paddock, Ethan A.; Prince, Mark E.; Strange, Mia; Sylvester, Michael J.; Thompson, Dana M.; Valdez, Tulio A.; et al.
Abstract : Academic centers embody the ideals of otolaryngology and are the specialty's port of entry. Building a diverse otolaryngology workforce—one that mirrors society—is critical. Otolaryngology continues to have an underrepresentation of racial and ethnic minorities. The specialty must therefore redouble efforts, becoming more purposeful in mentoring, recruiting, and retaining underrepresented minorities. Many programs have never had residents who are Black, Indigenous, or people of color. Improving narrow, leaky, or absent pipelines is a moral imperative, both to mitigate health care disparities and to help build a more just health care system. Diversity supports the tripartite mission of patient care, education, and research. This commentary explores diversity in otolaryngology with attention to the salient role of academic medical centers. Leadership matters deeply in such efforts, from culture to finances. Improving outreach, taking a holistic approach to resident selection, and improving mentorship and sponsorship complement advances in racial disparities to foster diversity.